Lateral Flow Assay as a Field Test for Sero-Diagnosis of Brucellosis in Small Ruminants - Kathiriya, Jaysukh B.; Shah, Nalinkant M.; Trangadia, Bhavesh J.; Sindhi, Samiullakhan H.; Javia, Bhavesh B.; Ghodasara, Sanjay (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Lateral Flow Assay (LFA) considered as a field diagnostic test for brucellosis in small ruminant. For the purpose, 268 whole blood samples (sheep-112 and goats-156) were collected from selected organized and scattered herds located in South Saurashtra region of Gujarat. Out of 112 sheep tested, 12 (10.71%), 8 (7.14%), 15 (13.39%), while from 156 goats tested, 24 (15.38%), 18 (11.54%), 25 (16.03%) were positive by Rose Bengal Plate Test (RBPT), Indirect Enzyme-Linked Immunosorbent Assay (iELISA) and LFA, respectively. The sensitivity of RBPT as compared to iELISA was 80.00% and 84.00%; and LFA as compared to iELISA was 53.33% and 64.00% in sera samples of sheep and goats, respectively. The specificity of RBPT and LFA was 100% in sheep for both these tests, whereas in goats sera samples it was 97.71% and 98.47% as compared to iELISA. The negative predictive value for RBPT was 97.00% and 96.97%; while for LFA it was 93.27% and 93.48% in sera samples of sheep and goats, respectively. However, positive predictive values (PPV) for RBPT were 100.00% and 87.85%; while for LFA 100.00% and 88.89% in sera samples of sheep and goats, respectively. McNemar chi-square test for independent data (with Yates’ correction) revealed non-significant difference between RBPT vs iELISA as 2.68% and 0.64%, while LFA vs iELISA as 6.25% and 4.45% in sera samples of sheep and goats, respectively. The concordance of iELISA with RBPT was k=0.874 and k=0.831; while for LFA k=0.664 and k=0.705 in sheep and goats, respectively. The performance of LFA is comparable to RBPT considering iELISA as gold standard, except sensitivity of LFA.